2019
DOI: 10.5194/nhess-2019-82
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Comprehensive Evaluation of the National Water Model (NWM) – Height Above Nearest Drainage (HAND) Flood Mapping Methodology

Abstract: Abstract. Flood maps are needed for emergency response, research, and planning. The Height Above Nearest Drainage (HAND) technique is a low-complexity, terrain-based approach for inundation mapping from elevation, discharge-height relationship, and streamflow data. The recent operational capacities of the NOAA National Water Model (NWM) and pre-processed HAND products from the University of Texas offer an operational framework for real-time and forecast flood mapping across the United States. This paper offers… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…That is, the model is more likely to generate false alarms than it is to miss areas of true inundation in the benchmark dataset. These performance metrics are comparable with those obtained in previous studies using models with more explicit computational complexity (Sampson et al, 2015;Sosa et al, 2020;Wing et al, 2017) or with similar sub-grid topographic representations (Johnson et al, 2019;Yamazaki et al, 2011).…”
Section: National-scale Comparisonssupporting
confidence: 87%
See 1 more Smart Citation
“…That is, the model is more likely to generate false alarms than it is to miss areas of true inundation in the benchmark dataset. These performance metrics are comparable with those obtained in previous studies using models with more explicit computational complexity (Sampson et al, 2015;Sosa et al, 2020;Wing et al, 2017) or with similar sub-grid topographic representations (Johnson et al, 2019;Yamazaki et al, 2011).…”
Section: National-scale Comparisonssupporting
confidence: 87%
“…After further extreme flooding in 2015-2016, the National Flood Resilience Review called for "a more integrated flood risk modelling approach to allow simulations to be run which link meteorology, hydrology and flooding across England" (Cabinet Office, 2016, p.26). To address these needs, simplified approaches have been applied to reduce computation time further, although their accuracy is yet to be evaluated fully (Afshari et al, 2018;Hall et al, 2003;Johnson et al, 2019;Nobre et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies assessing NWM analysis also reported similar negative biases. Johnson et al, (2019), for example, found that the inundation maps generated by combining NWM 1.2 reanalysis with the HAND method (Nobre et al, 2016) underpresernted the extent of inundation, and cited the underprediction of streamflow by NWM as one of the primary causes. It should be noted, however, that this underprediction can be at least partially explained by the negative biasse in NLDAS-2 precipitation data during these events -there is a negative bias in the NLDAS precipitation data evident in major storm events that is indicative of data quality issues.…”
Section: Discussionmentioning
confidence: 99%
“…As NWM is a relatively new model, to date only limited works have touched on its performance, and few of these focused on the skills of NWM vis-à-vis simpler, conceptual models (Nobre et al, 2016, Hansen et al, 2019Johnson et al, 2019;Viterbo et al, 2020a;2020b). Loosely related, there is a body of literature on relative performance of physicallybased, distributed and lumped, conceptual hydrologic models.…”
Section: Introductionmentioning
confidence: 99%